Screening and Identification of Bacteria Isolated from Giant Freshwater Prawn (Macrobrachium rosenbergii de Man) - บุตรดี อรวรรณ์; อู่สุวรรณ พรพรรณ; สอนสนิท กัญญา (KKU Science Journal, 2013)
In this study, the preliminary character of probiotic bacteria which were isolated from the gastrointestinal tract of Giant Freshwater Prawn (Macrobrachium rosenbergii de Man) from natural canel in Nakhon Pathom province Thailand were studied. Out of 442 isolates of gram positive bacteria detected were tested for growth inhibition activity against 4 pathogenic bacteria which were Aeromonas hydrophila, Escherichia coli, Vibrio harveyi and Vibrio parahaemolyicus by Agar Well Diffusion Assay method. The result showed that 8 isolates of Bacillus species were able to form clear zone. Five isolates grew rapidly and covered the pathogenic-bacterial colonies. The genetic analysis by 16S rRNA gene sequenceing identified that all bacterial isolates are B. pumilus TSN33, B. pumilus RBM499, B. subtilis TSM33, B. subtilis TSM262, B. subtilis LLBM241, B. subtilis TSN262, B. aryabhattai TSM362, B. amyloliquefaciens TSN63, B. amyloliquefaciens TSM499-4, B. cereus HMN142, B. cereus LLBM202, B. thuringiensis HMN151 and B. licheniformis HMN152. These bacteria can be selected as the probiotic agents for giant freshwater prawn.